Pengembangan Sistem Informasi Pemesanan dan Pembayaran Tempat Kost Kawasan UMS Berbasis Web Dengan HTML5 - Setyawan, Fajar Juli; , Dr. Heru Supriyono, M.Sc (2015)
Lack of information about the program in ums make students have difficulties in finding the program, especially for students that their domicile is farther from the ums. Besides, the lack of promotion of boarding house owners through the internet makes information about the boarding house in ums cannot be reached by the students. Based on those reasons, the writer will develop reservation information systems and boarding house payment in ums applying the web by html5 basis. The making of web application basis is developing the exist application during this time which is conducted more appropriately according to the needs of the user and the boarding house owners involved. Research is conducted using system development life cycle (SDLC) method by a waterfall model and using the php programming, html5, css, database mysql also javascript which will maximize the function of html5, which html5 is convinced to be able to provide facilities for the making of web application basis with new tag-tag on it. The result of testing is done by blackbox way, comparing on various web browsers and promoting to the user candidate. The results of testing shows that website can run well without any significant obstacles, this website is compatible in a web browser like mozila firefox and google chrome also obtained percentage value 66,6 % for do agree and 33.3 % for agree that these information systems can ease in finding a boarding house.